Sexual Dimorphism of Shell Turtles (Cuora amboinensis) in the Ex-situ Conservation Area, Bengkulu University, Sumatra - Rezki Nopantri; Bhakti Karyadi; Deni Parlindungan; Sutarno Sutarno; Aceng Ruyani; A. A. Sukarso (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
This research aims to determine the physical differences between male and female turtles based on the secondary morphological characteristics of Cuora amboinensis. The method used in this research is a visual method with metric data presented in photos and measurement data, with a sample size of 20 individuals consisting of 12 females and 8 males. The research was carried out in September–December 2023 at the biodiversity study center at Bengkulu University. Observation results identified male C. amboinensis turtles with larger heads and brighter chins than female turtles. The carapace is oval with small bumps on vertebral 5 and wider marginal edges than in female turtles; the male's plastron displays a distinctive concave while the females have a flatter plastron. Male turtles have longer and thicker tails than female turtles. There are differences in the morphological characteristics of male and female C. amboinensis turtles, specifically in the head, carapace, plastron, and tail morphology.